Descriptive Study on Demographic Factors and Performance Strategies among Athletes - N.M., Fauzan, Ghazali,; N., Anuar; Aden, E. (2017)
The purpose of this research is to investigate the differences in demographic factors and performance strategies among athletes. The demographic factors such as gender, years of study and years of involvement in sports played an important role in the use of performance strategies in determining their performance strategies in sports. The instruments used for this research is Test of Performance Strategies (TOPS) to measure the performance strategies. The finding shows that the demographic factors significantly differences on performance strategies. In general the result showed the demographic factors such as; gender at t (21) = 13.75; p < .05; years of study at t (21) = 9.46; p < .05 and years of involvement at t (20) = 11.37; p < .05 with performance strategies. The above results showed that the demographic factors revealed statistically significantly differences with performance strategies. In addition, the demographic factors also showed the significant differences with all sub factors in performance strategies such as goal setting, relaxation, activation, imagery, self talk, attentional control, emotional control and automaticity. The implication of this research is, in sports the demographic factors played an important role in determining their performance strategies. In order to enhance their ability and competency in sports performing they have to be trained in different style according to their age, gender, years of study and years of involvement.